Utilization of hypofractionated radiotherapy for breast cancer among Indonesian Radiation Oncologists during and after pandemic COVID-19 - Nugroho, Rafiq Sulistyo; Bani Kuncoro, Elia Aditya; Huswatun, Aida Lufti (Radioterapi & Onkologi Indonesia, 2024)
Background: The incidence of breast cancer (BC) increases over time. However, the availability of radiotherapy machines is minimal, especially after the COVID-19 pandemic. Hypofractionated radiotherapy (HFRT) may provide a solution for this situation. We intended to evaluate the practice of HFRT for BC patients amongst the Indonesian Radiation Oncologist Society members.Material and methods: This study uses a Google Form questionnaire distributed personally in early October 2021. Statistical analysis uses descriptive and Chi-square/Fisher tests.Results: Twenty-nine participants filled out the questionnaire. One-third of participants worked at Academic Hospital and were aged 35 - 45 years old. Most of the participants had working experience of fewer than ten years. 4 (13.8 %) and 3 (10.3 %) participants preferred HFRT for WBI with or without regional node irradiation. Only one participant selected HFRT for PMRT. 9 (31 %) and 8 (27.5 %) participants chose both HFRT and CFRT for postmastectomy with or without reconstruction. Conclusion: The utilization of HFRT in routine practice amongst Indonesian RO is still low despite proven clinical benefits. Continuing medical education about evidence-based may increase the translation of clinical trials into daily practice.